Applying the PNI Modified to Assess Tourist Needs Priority for Tourism Components Management - Yakampom, Vilaiporn; Meesuptong, Jaruporn; Kokanuch, Anchalee (KKBS Journal of Business Administration and Accountancy, 2025)
This research aimed to prioritize tourists’ needs concerning tourism management components and to analyze the discrepancies between tourists’ expectations and the current situation of these components in the Ban Na Wiang Yai Community, Dan Sai District, Loei Province. A sample of 369 tourists visiting the Ban Na Wiang Yai Community and the Phi Ta Khon Mask Museum in Dan Sai District, Loei Province, was selected using convenience sampling. Data were collected via questionnaires. Statistical analyses included percentages, mean, standard deviation, the Modified Priority Needs Index (PNI Modified), and paired samples t-tests. The findings revealed that English signage was the most pressing need, followed by travel safety management and the availability of sufficient restaurants. A comparison between expectations and the current situation regarding tourism management components showed statistically significant differences across all aspects. The outcomes of this research offer substantial benefits for shaping community tourism development. Specifically, they provide valuable input for relevant government and provincial tourism agencies, assisting them in formulating practical tourism development policies within the area.